-6x+2(2x-15)=-6

Simple and best practice solution for -6x+2(2x-15)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+2(2x-15)=-6 equation:


Simplifying
-6x + 2(2x + -15) = -6

Reorder the terms:
-6x + 2(-15 + 2x) = -6
-6x + (-15 * 2 + 2x * 2) = -6
-6x + (-30 + 4x) = -6

Reorder the terms:
-30 + -6x + 4x = -6

Combine like terms: -6x + 4x = -2x
-30 + -2x = -6

Solving
-30 + -2x = -6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + -2x = -6 + 30

Combine like terms: -30 + 30 = 0
0 + -2x = -6 + 30
-2x = -6 + 30

Combine like terms: -6 + 30 = 24
-2x = 24

Divide each side by '-2'.
x = -12

Simplifying
x = -12

See similar equations:

| -3(-2x+5)=17 | | -1.2=13x-18 | | 2y+12=66 | | z^2+14z=-45 | | X*240=12 | | 6=35 | | -6x-3(-3x+17)=-36 | | (5s+6)(s-2)= | | -7(4-4x)=-168 | | 8(t-2)+6t=7(2t+3)-9 | | -6(-7x-1)-x=-158 | | 7n-15=-16+8n | | -4x-6(-2x+15)=-10 | | 1/2(4/3)(3.14)(2.5)^3 | | -2x-3=2x+9 | | 4(6n-7)=140 | | 3(x-1)=7+5 | | n^2+9=34 | | Y=29(3)x | | 4(6n-7)=40 | | Y=29(3) | | 2/3x12/11 | | (n-6)(n-4)= | | 2j-12=2 | | -5.7=1.9+1.9z | | 4n-3=29+8n | | 2x-52=88 | | 8x-11+15x+3x+9=180 | | -5x-4(-x-17)=76 | | y+7=7(x-2) | | -10(b+645)=-490 | | 15-1/2b= |

Equations solver categories